Konsepsi Hak Menguasai Oleh Negara Atas Sumberdaya Agraria - mukmin zakie (Fakultas Hukum Universitas Islam Indonesia, 2005)
The ideal aspiration which exists in the Authority Rights of a State conception is to place the State as a party who has the authority to regulate the use of the State property to the welfare of the society. The Aspiration requires a neutral State which is free from the interest of others, except the interest of social welfare. However, In the reality, State is not neutral from intervention of individual Interest or a group of people Interest on behalf of the public interest. Thus, the promise of the State to grant welfare to the society is merelyn on the normative level.